تكوین السلطة التشریعیة كوجه من أوجه العلاقة بین السلطتین التنفیذیة والتشریعیة في النظام الأردني - الطراونة، مھند صالح (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2017)
يعتمد النظام الدستوري الأردني في مبادئه على قواعد النظام البرلماني التي تقوم على دعامتين أساسيتين، أولها ثنائية السلطة التنفيذية المكونة من الملك غير المسؤول سياًسياً والذي يمارس صلاحياته من خلال الوزراء ، ومن الوزارة المسؤولة سياسيا أمام البرلمان ، والدعامة الثانية هي طبيعة العلاقة بين العلاقة بين السلطتين التنفيذية والتشريعية، حيث تمتاز هذه العلاقة بالتعاون والتوازن بين السلطتين التنفيذية والتشريعية، وفي التطبيق والممارسة لدى النظام الدستوري الأردني يلاحظ أن هناك فجوة بين النظرية والتطبيق تتجسد في رجحان دور السلطة التنفيذية على حساب السلطة التشريعية مما سبب خلل في التوازن بين السلطات ، ولعل من أهم الأسباب التي أدت إلى رجحان كفة السلطة التنفيذية على حساب السلطة التشريعية امتلاك السلطة التنفيذية بعض الوسائل الدستورية المباشرة وغير المباشرة والتي لعبت من خلالها السلطة التنفيذية الدور الكبير في تكوين السلطة التشريعية بشقيها مجلس النواب والأعيان، وقد تعاظم هذا الدور من خلال طبيعة قوانين الانتخاب المتعاقبة ونظم تقسيم الدوائر الانتخابية ،وكذلك الآلية التي يتم من خلالها تكوين مجلس الأعيان الشق الثاني للسلطة التشريعية ،وعليه تحاول دراستنا تسليط الضوء على هذه الوسائل وبيان ودورها في تكوين السلطة التشريعية بشقيها مجلسي الأعيان والنواب وكيف أدت هذه الوسائل إلى إحداث خلل في منظومة العلاقة بين السلطتين التنفيذية والتشريعية.
Jordan's constitutional system is based on principles of the parliamentary system, the rules of which are based on two main pillars, the first of a bilateral executive branch consisting of the King is in charge politically and who exercises his powers through his ministers, and the ministry responsible politically before the Parliament, and the second pillar is the relationship between the authorities of the State in particular trait the relationship between the executive and the legislature, where the relationship characterized by cooperation and balance between the executive and the legislature, and in practice, and practice the Jordanian constitutional order notes that there is a gap between theory and practice is reflected in the preponderance of the role of the executive branch to the legislative branch account, causing an imbalance in the balance of powers, and perhaps of the main reasons that led to the preponderance of the executive branch to the legislative branch account of having the executive branch some of the direct and indirect means, which played in which the executive branch in the composition of the legislature, both the House of Representatives and the Senate, has been growing this role through the nature of the election laws of the successive systems districting election, as well as the mechanism by which the composition of the Senate second part of the legislative authority, and it is trying our study highlight the means and the statement and its role in the formation of the legislature, both Senate and the House of Representatives and how these methods have led to an imbalance in the relationship between the executive and legislative branches system
Keywords: السلطة التشریعیة -- السلطة التنفیذیة -- البرلمان -- مجلس الأعیان -- الأردن